Possible use of alcohol vapors by inhalation in the treatment of COVID-19 in clinical ill patients - Islam, Saif ul (International Journal of Basic & Clinical Pharmacology, 2020)
Ethyl alcohol or ethanol is an effective chemical in denaturing enveloped viruses in vitro, including SARS-CoV-2. It is found that exposure of only 30 seconds is sufficient to deactivate the virus. Alcohol has never been used for the treatment of viral lung infection. However, alcohol vapors by inhalation are used for acute respiratory distress syndrome and alcohol withdrawals.